2022
DOI: 10.3390/polym14091774
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Polymeric ARGF-Based Fly Ash-Concrete Composites: A Study for Eco-Friendly Circular Economy Application

Abstract: At present, low tensile mechanical properties and a high carbon footprint are considered the chief drawbacks of plain cement concrete (PCC). At the same time, the combination of supplementary cementitious material (SCM) and reinforcement of fiber filaments is an innovative and eco-friendly approach to overcome the tensile and environmental drawbacks of plain cement concrete (PCC). The combined and individual effect of fly ash (FA) and Alkali resistance glass fiber (ARGF) with several contents on the mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…According to Chen et al [ 69 ], Mg 2+ and SO 4 2− may be more damaging to the compressive strength of cement-based composites than other anions. The major damage caused by SO 4 2− to concrete is crystalline corrosion [ 6 , 70 ], which includes the conversion of thenardite crystals to mirabilite crystals [ 70 , 71 ] and the volume expansion of ettringite crystals and gypsum crystals. Both of the aforementioned factors may cause a sequence of physical and chemical reactions inside the concrete, which may result in additional concrete expansion and cracking [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chen et al [ 69 ], Mg 2+ and SO 4 2− may be more damaging to the compressive strength of cement-based composites than other anions. The major damage caused by SO 4 2− to concrete is crystalline corrosion [ 6 , 70 ], which includes the conversion of thenardite crystals to mirabilite crystals [ 70 , 71 ] and the volume expansion of ettringite crystals and gypsum crystals. Both of the aforementioned factors may cause a sequence of physical and chemical reactions inside the concrete, which may result in additional concrete expansion and cracking [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The building industry is responsible for around a quarter of all CO 2 emissions [ 3 ], not to mention the loss of non-renewable resources [ 4 ]. As a result, the building industry must innovate to ensure customer satisfaction, while also being environmentally sustainable, hence the interest in creating an eco-construction technique [ 5 , 6 , 7 ]. This unique design technique strives to produce pleasant structures at a reduced environmental cost by using more efficient materials [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of fly ash into UHPC has been extensively studied. Previous research studies underscored its potential to enhance concrete's mechanical properties and contribute to sustainability in the construction industry [16][17][18]. Studies have demonstrated that substituting 10% to 40% of cement with fly ash in UHPC formulations can significantly boost the material's strength and durability.…”
Section: Introductionmentioning
confidence: 99%
“…One of the materials that can be used to mix concrete is coal dregs, which have a high buildup, namely fly ash. Fly ash is industrial waste produced from burning coal and consists of fine particles [2], [4], [6]- [10]. Using coal as an energy source will produce ash, namely fly ash and bottom ash.…”
Section: Introductionmentioning
confidence: 99%